Myanmar's enemy within : Buddhist violence and the making of a Muslim 'other' - Wade, Francis (London, UK : Zed Books Ltd, 2019)
Explores the growing divide between Myanmar's Buddhist and Muslim communities, and questions why some of the most respected and articulate voices for democracy in the country have become complicit in the persecution of its religious minorities.
Includes bibliographical references (pages 407-419).
Refugee Studies Unit (RSU), CPJ
Book Finder International
Keywords: Islam and state -- Burma; Islam -- Relations -- Buddhism; Buddhism -- Relations -- Islam; Buddhism and state -- Burma; Burma -- Social conditions -- 1988-; Burma -- Politics and government -- 1988-; Burma -- History -- 1988-